The effects of banana waste biochar on soil macronutrient and growth performance of aerobic rice / Izzainur Ismail - Ismail, Izzainur (Faculty of Plantation and Agrotechnology, 2015)
Application of biochar is commonly reported to improve crop yield and enhance soil quality. This study was carried out to determine the effects of various banana waste biochar on soil macronutrient and the growth performance of aerobic rice. The experimental units were arranged in complete randomized design (CRD). It consists of five treatments and four replications. Aerobic rice seedlings were grown in soil treated with different types of biochar of the same amount which is 62.10 g fpot. The treatments are without biochar (TO), banana peel (BP) biochar (T1), banana leaves (BL) biochar (T2), 1:1 ratio of BP and BL (T3), and rice husk (RR) biochar (T4). All treatments received recommend NPK fertilizer of 0.414 g/pot. The banana peel and leaves was produced by pyrolysis process at 340°C for four hours, while rice husk biochar was obtained from Sekinchan, Selangor. The results of pH reading of biochar for Tl, T2, T3 and T4 is alkali range 7.50 to 8.54. The analytical result for plant height (cm) shows that the trend TI and T4 increase start from week 4th until the week 9th. The number of tiller for T1 is increased at 4th week until 6th week and remained constant until 9th week. The number of leaves for T0 increased from 4th week until 7th week and then decreased at 9th week. The number of panicle for all treatments increased with time. Dry matter weight (g) ofT3 is higher than compare to other treatments. Macronutrient content in soil shows that there is no significance difference among treatments. Among all treatments, T3 and T1 produced the highest filled grain weight 2.8 g compared to T0, T2, and T4.